Quality assessment of physical education program of state universities in the Philippines - Panganiban, Teejay Dela Cueva (Universitas Nusantara PGRI Kediri, 2019)
This descriptive-evaluative research was undertaken to assess the physical education program of five state universities in Region IV–A by 28 administrative staff, 69 faculty members, and 390 students. The study used the whole population of administrative staff and faculty members while Slovin’s formula was used to determine the sample size for students. Using self-made questionnaire and appropriate statistical measures, the results revealed a high level of awareness on physical literacy as an essential foundation of physical education among faculty members. The assessments of the faculty and student-respondents on Physical Education along with teacher education, supply and development was excellent and revealed a non-significant difference among the assessment made by administrative staff, faculty members and students. Moreover, the assessment on teacher education, supply and development, facilities and resources, and curriculum flexibility were found to be predictors of Physical Education program with curriculum flexibility as the best predictor. This study calls for enrichment of Physical Education Program to achieve quality delivery of the program.